Planning pedagogical impact of different orientation in personal and developmental education students by means of systematic physical training - Volkov V.L (Kharkov National Pedagogical University, 2011)
We consider the problem of training aimed at comprehensive development of personality of students by means of physical training. The study involved girls 17-19 years (n = 267) who are studying at the Pedagogical University. Determine the direction of teacher effects, which provide all-round harmonious development of physical and personal skills. The content of theoretical training of students in independent work. The correlation of the volume of physical activity of different orientation for girls who enrolled in the study group on physical education.